TRAINING THE CRITICAL THINKING SKILLS OF STUDENTS USING THE PROBLEM SOLVING LEARNING MODEL IN CHEMICAL EQUILIBRIUM - melysa pramitha rosa; Utiya Azizah (JCER (Journal of Chemistry Education Research), 2020)
The purpose of its research for  train students' critical thinking with problem solving learning models of equilibrium theory. The research was conducted in XI MIPA 1 class at SMA Negeri 14 Surabaya using the One Group Pretest Posttest Design method. The results obtained in this study were the teacher's implementation of the syntax in accordance with the problem solving learning model obtained by a percentage of â‰¥61% at each meeting. The student's relevant activity reaches a percentage of 82.78% for meeting 1; 84.44% for meeting 2, and 85% for meeting 3. At the time of the critical assessment of the 4 indicators drilled namely, interpretation, analysis, inference, and increasing understanding of 93.49% respectively; 82.87%; 88.90%; 85.42%. On the learning outcomes of students in the realm of knowledge by 92%. This shows the application of effective problem solving learning models in learning chemical equilibrium in training critical thinking skills.